Telaah Kecurangan dengan Fraud Diamond pada Lembaga Keuangan Syariah non Bank dalam Suatu Studi Literatur - Abdullah, Ikhsan; Lubis, Arnida Wahyuni (Bursa : Jurnal Ekonomi dan Bisnis, 2023)
Islamic corporate entities are currently increasing in foreign countries. People are starting to turn to the sharia economy. The sharia pawnshop office is one of the non-bank Islamic financial institutions that provides loans to consumers based on the sharia concept. A corporate entity must be supported by reports and reliable apprentice financial supervision to prevent fraud. Because it will have an impact on the level of trust in the company. However, due to the fact that there is fraud that occurs in pawnshops in several places. This study tries to examine the fraud by using a fraud diamond which consists of: Opportunity, Pressure, rationalization and ability. This study uses qualitative methods using descriptive methods. Research using documentation techniques. Documentation technique for analyzing documents related to non-bank Islamic Financial Institutions, diamond fraud. The data used in the analysis include Islamic banking books, Front Diamond, research articles and so on Based on the results of the research conducted, it is found that there are still frauds committed by employees and company leaders in several regions. The loss to the government reached Rp. 6.3 billion. Judging from the cases that occur, if examined using a fraud diamond, there are elements of pressure and opportunity that occur. It is hoped that the company will improve its internal control system and create a new system to prevent fraud and rotate positions to minimize fraud